A rare case of neoplastic transformation in a longstanding case of fistula-in-ano - Gupta, Neeru; Gupta, Chhaya; Sud, Aruna (Annals of Pathology and Laboratory Medicine, 2015)
MucinousÂ adenocarcinomaÂ developmentÂ inÂ aÂ longÂ standingÂ caseÂ ofÂ withÂ fistula-in-anoÂ isÂ rare.Â AÂ caseÂ of fistulaâ€“in-ano diagnosed as low gradeÂ mucinous adenocarcinoma on biopsyÂ andÂ confirmedÂ on ImmunohistochemistryÂ isÂ discussed. It was establishedÂ thatÂ theÂ carcinomaÂ hadÂ developed within theÂ fistulaÂ andÂ was notÂ aÂ secondary manifestationÂ ofÂ anyÂ otherÂ tumor.